Assistance in Preparing Simple Bookkeeping and MSME Taxation for the East Java Fatayat Business Group - Nugroho, Wawan Cahyo; Yani, Prawita; Susila, Muktar Redy; Widiarto, Hermono (Santoso Academy Network, 2024)
The Pawon Urip Program in Lumajang Regency is community empowerment in terms of food security and community nutrition with the aim of empowering the socio-economic sector of the Pejarakan Village community. Physical observations, social observations, and interviews, as well as exploratory descriptive analysis, were used to answer the research objectives. The economy of the people of Pejarakan Village is classified as lower middle class; this, of course, cannot be separated from the influence of less than optimal levels of education and land use; the social phenomenon of apathy is also reflected when people are too busy. Pawon Urip planting actually provides benefits to the community; although insignificant, all the processes that go through until the results can be enjoyed have an impact on the knowledge, psychological, and economic aspects of the community. The managerial implication in this research is that with assistance, MSME owners will better understand the basics of accounting and taxation, which will help them prepare their books correctly. Good bookkeeping will also help increase financial transparency and may impact investor or lender confidence. With accurate financial data, MSME management can make better business decisions. Whether in terms of investment, expenses, or other business strategies.